Retraction: Impact of coated phycocyanin and phycoerythrin on antioxidant and antimicrobial activity of soap, anti-acne face wash and hand sanitizer gel - Bahareh Nowruzi; Hossein Hashemi (Journal of Cosmetic Medicine)
Thread-lift procedures are becoming increasingly popular for treatingof skin laxity, particularly in the neck and submental regions. However, these procedures carry risks, including potential nerve injury, which can result in sensory and motor deficits. To document unusual complications following a thread-lift procedure and highlight the importance of understanding the complex anatomy of the neck and submental region to prevent such complications. A 40-year-old woman presented with concurrent unilateral weakness and numbness on the right side of her neck, including loss of the platysmal band and paresthesia behind the earlobe. The patient was evaluated clinically, and imaging studies were conducted to assess the extent of the nerve injury. The patient previously underwent a thread-lift procedure, including inserting lifting threads from behind the ears using sharp needles and absorbable threads, with one thread per side. Despite gradual improvement in sensation, muscle weakness and loss of the platysmal band persisted for approximately two months post-procedure. Further evaluation revealed that the patient experienced compression or minor injury to the greater auricular nerve (GAN), leading to neurapraxia (grade 1) and loss of sensation behind the right ear. In addition, the cervical branch of the facial nerve (CBFN) has been implicated in muscle weakness and platysmal band loss. This case underscores the importance of understanding the intricate anatomy of the neck and submental region to avoid injury to critical structures such as the GAN and CBFN. Adopting techniques such as working within the sub-platysma plane and using up to 0.4 mm diameter threads with blunt cannulas may help mitigate the risk of nerve damage. This report highlights the need for meticulous surgical practice and ongoing professional development to ensure the safety and efficacy of thread-lift procedures.